2017
DOI: 10.1186/s12943-017-0679-7
|View full text |Cite
|
Sign up to set email alerts
|

The long non-coding RNA BC200 (BCYRN1) is critical for cancer cell survival and proliferation

Abstract: BackgroundBC200 is a long non-coding RNA expressed at high levels in the brain and elevated in a variety of tumour types. BC200 has a hypothesized role in translational regulation; however, to date the functional role of BC200 in both normal and diseased states remains poorly characterized.MethodsDetailed BC200 expression analyses were performed in tumor cell lines, primary and non-tumorigenic cultured breast and lung cells, and a panel of normal human tissues by quantitative real-time PCR and confirmed by nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
79
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 31 publications
(72 reference statements)
9
79
0
Order By: Relevance
“…It is universally expressed in the nervous system, as well as in several cancers . BC200 expression is elevated in proliferating cultured cells, making it a promising therapeutic target for a broad spectrum of cancers . Our results showed a significant upregulation of BC200 by EBV, revealing, for the first time, the relationship between BC200 and EBV.…”
Section: Discussionsupporting
confidence: 50%
“…It is universally expressed in the nervous system, as well as in several cancers . BC200 expression is elevated in proliferating cultured cells, making it a promising therapeutic target for a broad spectrum of cancers . Our results showed a significant upregulation of BC200 by EBV, revealing, for the first time, the relationship between BC200 and EBV.…”
Section: Discussionsupporting
confidence: 50%
“…Recently, it has been reported that abnormal expression of BCYRN1 has an impact on varieties of human cancers [19,24,25]. However, the regulatory mechanism of BCYRN1 is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of lncRNA BCYRN1 has been found in various cancers, as well as in neurodegenerative diseases [18,19]. However, the clinical role of BCYRN1 and its biological functions in CRC remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies focus on its potential molecular targets by immunohistochemistry . Recently, increasing evidences showed that carcinogenesis of various cancers are closely associated with abnormal expression of lncRNAs . So far, no study attempts to reveal the significance of lncRNA expression in EACSCC to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%